How do you simplify (6^3 - 9 - 1)(63−9−1) using order of operations? Algebra Expressions, Equations, and Functions PEMDAS 1 Answer Bio Jan 12, 2016 206 Explanation: 6^3-9-1 = 216-9-163−9−1=216−9−1 = 207 -1=207−1 = 206=206 Answer link Related questions What is PEMDAS? How do you use PEMDAS? How do you use order of operations to simplify 3(7-2)-83(7−2)−8? What are common mistakes students make with PEMDAS? How do you evaluate the expression 5[8+(3-1)]-25[8+(3−1)]−2? How do you simplify the expression 4(30-(3+1)^2)4(30−(3+1)2)? How do you evaluate the expression x^4+xx4+x if x=2? Is it okay to add first before subtracting in 4-6+34−6+3? How do you simplify (-3)^2+12*5(−3)2+12⋅5? How do you simplify (4-2)^3-4*8+21div3(4−2)3−4⋅8+21÷3? See all questions in PEMDAS Impact of this question 1430 views around the world You can reuse this answer Creative Commons License